A castration parasite of an ant-plant mutualism - Yu, D. W. (1998)
Exploring the factors governing the maintenance and breakdown of cooperation between mutualists is an intriguing and enduring problem for evolutionary ecology, and symbioses between ants and plants can provide useful experimental models for such studies. Hundreds of tropical plant species have evolved structures to house and feed ants, and these ant–plant symbioses have long been considered classic examples of mutualism. Here, we report that the primary ant symbiont, Allomerus cf. demerarae, of the most abundant ant-plant found in south-east Peru, Cordia nodosa Lam., castrates its host plant. Allomerus workers protect new leaves and their associated domatia from herbivory, but destroy flowers, reducing fruit production to zero in most host plants. Castrated plants occupied by Allomerus provide more domatia for their associated ants than plants occupied by three species of Azteca ants that do not castrate their hosts. Allomerus colonies in larger plants have higher fecundity. As a consequence, Allomerus appears to benefit from its castration behaviour, to the detriment of C. nodosa. The C. nodosa–ant system exhibits none of the retaliatory or filtering mechanisms shown to stabilize cheating in other cooperative systems, and appears to persist because some of the plants, albeit a small minority, are inhabited by the three species of truly mutualistic Azteca ants.